2014
DOI: 10.1093/abbs/gmt117
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTAIR in carcinogenesis and metastasis

Abstract: Long non-coding RNAs (lncRNAs) have gained massive attention in recent years as a potentially new and crucial layer of gene regulation. LncRNAs are prevalently transcribed in the genome, but their roles in gene regulation and disease development are largely unknown. HOX antisense intergenic RNA (HOTAIR), a lncRNA located in the HOXC locus, has been shown to repress HOXD gene expression and promote breast cancer metastasis. Mechanistically, HOTAIR interacts with and recruits polycomb repressive complex 2 (PRC2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
130
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 32 publications
2
130
1
4
Order By: Relevance
“…Several recent studies have identified the aberrant expression of HOTAIR in a number of cancer types, including breast, colon, bladder, renal, pancreatic, cervical and lung cancer, and a high level of HOTAIR expression has been correlated with enhanced breast, colon and gastric cancer metastasis. In addition, HOTAIR-knockdown is able to inhibit the invasion and proliferation of cells, as well as altering cell cycle progression and inducing cells apoptosis, thus indicating that HOTAIR may function in the modulation of cancer progression (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have identified the aberrant expression of HOTAIR in a number of cancer types, including breast, colon, bladder, renal, pancreatic, cervical and lung cancer, and a high level of HOTAIR expression has been correlated with enhanced breast, colon and gastric cancer metastasis. In addition, HOTAIR-knockdown is able to inhibit the invasion and proliferation of cells, as well as altering cell cycle progression and inducing cells apoptosis, thus indicating that HOTAIR may function in the modulation of cancer progression (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies suggest that their expression patterns are even more tissue-specific than those of protein-coding genes (Cabili et al 2011) and that they are involved in pivotal tumor suppressive and oncogenic pathways. Increased expression of the lncRNA HOTAIR in primary breast tumors, for instance, was shown to strongly correlate with metastasis and death (Gupta et al 2010), with similar up-regulation and prognostic significance observed in a number of other cancers, including nonsmall cell lung cancer and pancreatic cancer (Zhang et al 2014). Similarly, overexpression of the lncRNA MALAT-1 has been linked to hepatocellular carcinoma and metastasis in small-cell lung cancer (Lin et al 2007).…”
Section: Introductionmentioning
confidence: 80%
“…According to their alternative expression pattern, certain lncRNAs may reflect the progress of disease, and may be regarded as independent predictors for cancer diagnosis (14,16,31,32). The overexpression of Hox transcript antisense RNA in breast cancer promoted metastasis (33,34) and homeobox A transcript at the distal tip is considered an indicator for determining the progress of pancreatic cancer (35). Prostate cancer associated transcript 1 identified in hepatocellular carcinoma has been associated with the prognosis in patients with hepatocellular carcinoma (36).…”
Section: Discussionmentioning
confidence: 99%